Gender differential in disease burder: Its role to explain gender differential in mortality - Biplab, Dhak; Mutharayappa, R. (Bangalore, 2009)
The present paper seeks to provide certain explanation in the Indian context, for the recently observed paradox in gender differential in health. There has been mismatch between gender differential in mortality and morbidity in terms of females experiencing a low rate of mortality despite being confronted with a high level of morbidity as compared to males, particularly from the age 30. Using multiple data sets, it has been observed that gender differential in diseases pattern, severity in illness and greater risk behaviour among males play an important role in explaining the paradox.
Keywords: Disease burden; Mortality - Gender Differential